Kinerja Proyek Ditinjau Dari Sistem Pengendalian Internal, Audit Internal Dan Efisiensi Beban Proyek: Studi Pada PT Maratama Cipta Mandiri - Restu Kiswanto; Catur Martian Fajar; Adi Suparwo (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2019)
The low performance in carrying out projects at PT Maratama Cipta Mandiri led to a decrease in project revenue, it can be proven that in practice there are still ineffective and efficient project implementation in the management system, audit results, and project costs. Referring to this, this study aims to determine the impact of internal control, internal audit, and the efficiency of project costs on project performance. The method used is a survey method with a quantitative approach, and descriptive verification research type. The data source used is primary data as a result of 88 questionnaires distributed to employees. The results of the study based on the partially proposed hypothesis shows that internal control has a significant positive effect on project performance, internal audit has no significant negative effect on project performance, the project load efficiency does not have a significant positive effect on project performance, and simultaneously internal control, internal audit, and project cost efficiency have a significant positive effect on project performance. Other results found that there are variables that have the greatest influence on project performance is internal control, with the accounting system dimensions of the accounting system design indicators. From the results of this study it is expected that the company can improve the internal control system so that it can improve the performance of the project at PT Maratama Cipta Mandiri.